O patrimônio vivo e a governança participativa: uma análise dos contextos brasileiro e estadunidense - Ana Beatriz Mascarenhas Pereira (2023)
Certainly, the concept of heritage has been changing over time. Since the “emergence” of historic monuments in the 15th century until today, these changes, a reflection of our understanding of what these assets are, have consequently altered the way we carry out their protection and maintenance. Despite the great progress in terms of involving the population in the nomination and listing process, the practice remains that its management is solely the responsibility of the State. Since cultural heritage is built collectively, the premise that its maintenance and management should be shared is also legitimate. In this sense, this work is based on two concepts that seek to guarantee the participation of the population both in the processes of protecting assets and in their management – the idea of living heritage and participatory governance. The first is based on the conservation of sites in which there is a direct association with the community that preserves it, since it is an intrinsic part of everyday life. This concept merges the tangible and intangible dimensions in a way that they are inseparable. In this way, the participatory governance of cultural assets, especially in urban areas of cultural interest, is a means for the deliberations and actions carried out by the community and advised by specialists, to have lasting, broad and sustainable effects. In order to test the hypothesis that the approaches of living heritage and participatory governance are essential and legitimate for the conservation of urban areas of cultural interest, since the involvement of the population only occurs until its indication or tipping, two neighborhoods were analyzed – East Boston, located in the city of Boston, Massachusetts, United States and Santa Tereza, in the city of Belo Horizonte, Minas Gerais, Brazil. Despite being economically, socially and culturally diverse contexts, both have very relevant identity values. At the same time, this distinction contributes to the investigation of the application of these approaches in such different scenarios.